Faktor-Faktor Yang Berhubungan Dengan Waktu Pulih Sadar Pasca General Anestesi Pada Bedah Saraf Di RSUD dr. Mohamad Soewandhie Surabaya - Asyiyah Rahmawati Putri; Sarka Ade Susana; Jenita Doli Tine Donsu (Journal of Applied Psychology and Health Studies, 2025)
Recovery time after general anesthesia is a crucial factor in the postoperative recovery of neurosurgical patients. Delayed recovery time increases the risk of complications such as airway obstruction, hypoxemia, and aspiration. Several factors can influence recovery time, including duration of surgery, intraoperative blood loss, and the type of anesthetic used This study aims to analyze the factors associated with recovery time after general anesthesia in neurosurgical patients at Dr. Mohamad Soewandhie General Hospital, Surabaya. This research employs an observational analytic design with a cross-sectional approach. The sample consists of 30 patients undergoing neurosurgery with general anesthesia. Data collection was conducted through direct observation and documentation review of patient medical records. Statistical analysis was performed using Spearman’s test and multiple linear regression to determine the most significant factors affecting recovery time. The study results indicate that duration of surgery and intraoperative blood loss significantly correlate with delayed recovery time (p=0.016 and p=0.035). Patients who underwent surgeries lasting more than four hours and experienced blood loss exceeding 1000 ml required more time to regain full consciousness compared to other groups. Conclusion: Duration of surgery is the most significant factor influencing recovery time after general anesthesia in neurosurgery. Therefore, careful monitoring of surgical duration and intraoperative blood loss is necessary to minimize delayed recovery risks.